Uji Performa Pertumbuhan Dan Profil Sel Darah Merah Ayam Broiler (Fase Starter) Yang Diberi Pakan Tepung Magot Bsf (Black Soldier Fly) Sebagai Pakan Tambahan Pada Ransum Komersial - Brechmans Nicolans Trison Ko'a; Frans U Datta; Heny Nitbani (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
This study aims to determine the effect of adding Black Soldier Fly (BSF) maggot flour at several levels (dose) in complete feed on feed consumption, ration conversion, growth (body weight gain) and red blood cell profile in broiler chickens. The research material used 100 chickens. This study used a Completely Randomized Design (CRD) with 4 treatments where each treatment was filled with 25 animals/treatment. Parameters observed were ration consumption, body weight gain, feed conversion and broiler blood cell profile. The data obtained will be presented in the form of a table and described descriptively. The results showed that the addition of Black Soldier Fly (BSF) maggot flour had an effect on body weight gain but did not show a significant difference between the treatment groups. The addition of BSF maggot flour did not affect the red blood cell profile where the total erythrocyte, hemoglobin, hematocrit and erythrocyte index showed normal values. The conclusion in this study was that the addition of maggot flour to commercial rations affected the degree of feed palatability, thus affecting the level of consumption and erythrocyte profile at the beginning of rearing and the addition of protein in the finisher phase had no effect on feed efficiency.